A Competency Model for Management Education for Sustainability. (June 2017) - Sharma, Radha R.
Management education needs transformation to avoid socio-economic volatility in this globalised world and to deal with the crises of responsibility and sustainability. Despite rising demand and increasing popularity, management education has been under scathing attack for eroding values and ethics, and focus on imparting knowledge and skills for improving the bottom line of the firms ignoring the triple bottom line. The value crisis leading to economic meltdown reinforced the need for a paradigm shift in management education, which required responsibility to be embedded in the management curriculum for sustainability. United Nation's supported 'Principles for Responsible Management Education' (PRME) initiative created a movement across the globe among scholars, practitioners and policy makers. The moot question arose "What are the competencies that need to be developed?" The article presents a competency framework and a (Cognitive, Affective, Moral and Behavioural competencies) CAMB competency model developed by the author (Sharma, 2015) based on the PRME principles which has been validated by scholar academics and practitioners from across geographies and can be adopted by business schools nationally and internationally.